2017
DOI: 10.1097/md.0000000000008072
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinases and physical exercise

Abstract: Background:Matrix metalloproteinases (MMPs), particularly gelatinase A (MMP-2) and gelatinase B (MMP-9), as well as their tissue inhibitors (TIMP-1 and TIMP-2), are involved in the development of skeletal muscle tissue, in the repair process after muscle injury and in the adaptive modifications induced by physical exercise in skeletal muscle. This paper aims at reviewing results from human studies that investigated the role of gelatinases and their inhibitors in skeletal muscle response to acute physical exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…Thus, these MMPs are of crucial importance for the development and repair of muscles after injury, as ECM components must be degraded to allow satellite cells to migrate to and, ultimately, fuse with existing myofibers [ 59 ]. In agreement with earlier studies examining their expression in muscle tissue [ 60 ], we found MMP2 levels to be virtually unaffected by acute exercise, irrespective of the modality used. Scheede-Bergdahl et al [ 61 ] found levels to be increased after 2 and 8 weeks of rowing exercise in both patients suffering from type 2 diabetes and healthy controls and suggested that prolonged exercise training may be required to increase MMP2 gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, these MMPs are of crucial importance for the development and repair of muscles after injury, as ECM components must be degraded to allow satellite cells to migrate to and, ultimately, fuse with existing myofibers [ 59 ]. In agreement with earlier studies examining their expression in muscle tissue [ 60 ], we found MMP2 levels to be virtually unaffected by acute exercise, irrespective of the modality used. Scheede-Bergdahl et al [ 61 ] found levels to be increased after 2 and 8 weeks of rowing exercise in both patients suffering from type 2 diabetes and healthy controls and suggested that prolonged exercise training may be required to increase MMP2 gene expression.…”
Section: Discussionsupporting
confidence: 92%
“…Recent observations provide evidence that gelatinase activity in the blood circulation can be considered mediators of inflammation and provide important information about inflammatory states during the aging process and pathological conditions (Giannakos et al, 2016 ; Nascimento et al, 2016 ; Lo Presti et al, 2017 ; Smigiel and Parks, 2017 ). High MMP-2 and MMP-9 activity may be related to immunity, tumor progression or apoptosis, rheumatoid arthritis, obesity and may play a role in cardiovascular disease diagnoses (Nascimento et al, 2015 , 2016 ; Giannakos et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that acute exercise at high altitude showed a different systemic effect on the circulating protein levels of MMP-9 and MMP-2 as well as their inhibitor TIMP-1, which suggests that these proteins might have very different time courses of expression/secretion/activity. Under normoxic conditions, MMP-9 concentrations immediately increased after acute exercise, while MMP-2 and TIMP-1 concentrations either increased or stayed unchanged (Lo Presti et al, 2017). A decrease in MMP-9 concentrations was only observed under hypoxic conditions without exercise stimulus (Rahat et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…processes are not yet well understood-gelatinase measurement in serum can be useful to detect the systemic response to acute exercise (Lo Presti et al, 2017). Furthermore, the loss of circulating MMP-9 concentrations could also implicate an attenuation of macrophage infiltration and collagen deposition in circulation (Luttun et al, 2004), but was not found to be any indicator of an exercise-induced change in muscular damage (Lo Presti et al, 2017). Circulating MMP-2 concentrations, however, were not associated with EC number.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation